Participatory Model of Student Da’wah Communication through Wall Magazine - Putriana Nur Faizah Putri; Achmad Arifulinnuha; Harry Purwanto; Shohenuddin (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
This study discusses a participatory model of student da'wah communication through wall magazines (mading) as an alternative to strengthening da'wah skills in the educational environment. The background of this study stems from the weak communication skills of students in da'wah, which tend to be monotonous and lack creativity, thus requiring participatory media that can encourage active involvement. The objectives of this study are to describe the forms of student participation in planning, producing, and evaluating mading dakwah, as well as to analyze its relevance to the theory of dakwah communication and participatory communication theory. This study uses a qualitative approach with a case study method, conducted at the PKBM PNF KBRI Kuala Lumpur. Data was obtained through observation, interviews, and documentation. The results of the study show that the process of communication of da'wah through wall magazines takes place participatively in five main stages, namely identification of message needs, joint planning, content production, distribution, and evaluation. This model combines elements of da'wah communication (da'i, mad'u, message, media, effect) with the principles of participatory communication (dialogical, inclusive, bottom-up, and empowering). Thus, this study concludes that wall magazines are effective as a participatory da'wah medium that empowers students as communicators and creators of da'wah messages.